2014
DOI: 10.1097/qad.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

Earlier initiation of ART and further decline in mother-to-child HIV transmission rates, 2000–2011

Abstract: MTCT rates in the UK and Ireland have continued to decline since 2006, reaching an all-time low of 5 per 1000 in 2010-2011. This was primarily because of a reduction in transmissions associated with late initiation or nonreceipt of antenatal cART, and an increase in the proportion of women on cART at conception.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
206
0
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 353 publications
(234 citation statements)
references
References 27 publications
18
206
0
10
Order By: Relevance
“…It is important to note that there were other complicating factors contributing to this case, and there were insufficient data to determine whether the transmission occurred intrapartum or not. Our findings are thus consistent with current overall MTCT rates [1] in this population, which are around 5 per 1000. Overall, infection status was available for 95% of infants over 18 months, with missing data largely due to recently-born infants awaiting infection status confirmation and not likely to result in substantial bias.…”
Section: Commentsupporting
confidence: 81%
See 2 more Smart Citations
“…It is important to note that there were other complicating factors contributing to this case, and there were insufficient data to determine whether the transmission occurred intrapartum or not. Our findings are thus consistent with current overall MTCT rates [1] in this population, which are around 5 per 1000. Overall, infection status was available for 95% of infants over 18 months, with missing data largely due to recently-born infants awaiting infection status confirmation and not likely to result in substantial bias.…”
Section: Commentsupporting
confidence: 81%
“…Overall, infection status was available for 95% of infants over 18 months, with missing data largely due to recently-born infants awaiting infection status confirmation and not likely to result in substantial bias. We have previously shown that cases reported at a later date did not affect transmission rates [1].…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2014, we reported that the national MTCT rate in the United Kingdom (UK) and Ireland had reached the all-time low of 0.46% in 2010-2011 [1]. With this update, we show a continued decline in recent years.…”
mentioning
confidence: 79%
“…Between 2006 and 2014, in the UK as a whole, the transmission rate for the approximately 11,000 children born to women living with HIV infection diagnosed prior to delivery was well under 1% [9]; another 75 infants were also born and diagnosed with perinatally acquired HIV whose mothers were not diagnosed prior to delivery [10].…”
Section: Antenatal Screeningmentioning
confidence: 99%